2019
DOI: 10.1111/joop.12276
|View full text |Cite
|
Sign up to set email alerts
|

A process model linking family‐supportive supervision to employee creativity

Abstract: In the current study, we strategically link the work–family literature to employee creativity, a construct seen as a linchpin for organizational success, through family‐supportive supervision based on the concept of reciprocity of interdependent exchanges within social exchange theory. In Study 1 (N = 188), based on data with a one‐month lag between two assessments, we demonstrate that family‐supportive supervision is an explanatory leadership behaviour that connects broader leadership styles (i.e., leader–mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 118 publications
0
11
0
Order By: Relevance
“…This research extends prior literature by explicating how suffering from family-to-work conflict may drive employees away from change-oriented citizenship behaviors, as well as how their access to valuable resources buffers this process. The relatively limited attention to this important topic is surprising, in light of the well-established argument that adverse situations at the family–work interface might be so energy-consuming and distracting for employees that they curtail discretionary efforts from which their employing organization otherwise could benefit (Beham, 2011; De Clercq et al, 2019; McKersie et al, 2019). With a basis in COR theory, I have investigated the buffering effects of four distinct resources—two embedded in peer relationships (social interaction and goodwill trust) and two informed by the fairness of the organization’s internal functioning (distributive and procedural justice).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research extends prior literature by explicating how suffering from family-to-work conflict may drive employees away from change-oriented citizenship behaviors, as well as how their access to valuable resources buffers this process. The relatively limited attention to this important topic is surprising, in light of the well-established argument that adverse situations at the family–work interface might be so energy-consuming and distracting for employees that they curtail discretionary efforts from which their employing organization otherwise could benefit (Beham, 2011; De Clercq et al, 2019; McKersie et al, 2019). With a basis in COR theory, I have investigated the buffering effects of four distinct resources—two embedded in peer relationships (social interaction and goodwill trust) and two informed by the fairness of the organization’s internal functioning (distributive and procedural justice).…”
Section: Discussionmentioning
confidence: 99%
“…For this study, family-to-work conflict is central, with the proposition that family-related strain spills over into the workplace and has harmful consequences for employees’ ability to perform discretionary work activities that require significant energy (Beham, 2011; Nohe et al, 2014). As previous studies show, the interference of family with work tends to leave employees with insufficient energy to perform their job duties (Witt & Carlson, 2006), be creative (McKersie et al, 2019), engage in OCB (Mercado & Dilchert, 2017), or help individual colleagues (De Clercq et al, 2019). In turn, this study seeks two main aims: (a) to explicate the role of family-to-work conflict as an understudied inhibitor of change-oriented citizenship behavior and (b) to specify the conditions in which this source of workplace adversity is less likely to escalate.…”
Section: Introductionmentioning
confidence: 99%
“…We found support for our hypotheses that supervisors who are engaged in FSSB are perceived as more warm and more competent. We proposed this because FSSB are discretionary behaviors that require effort from the supervisor to demonstrate not only interpersonal competence but also empathy and caring behaviors toward employees (McKersie et al, 2019). This has important implications for SCM as it suggests that individuals in mixed-stereotyped groups can change how others stereotype them by behaving in ways that are inconsistent with the mixed stereotype (Eagly & Wood, 2012;Jarreau et al, 2019).…”
Section: Theoretical Contributions and Implicationsmentioning
confidence: 99%
“…In addition to reducing the negative effects of psychological strain, family‐specific support also has an enhancing effect on positive outcomes for employees. These include employee well‐being (Hammer, Kossek, Anger, Bodner, & Zimmerman, 2011; Lapierre & Allen, 2006), work engagement (Rofcanin et al., 2021), creativity (McKersie, Matthews, Smith, Barratt, & Hill, 2019), thriving at work (Russo, Buonocore, Carmeli, & Guo, 2018), and physiological outcomes such as sleep quality (Crain et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the evident benefits for the home domain (see Kossek et al, 2011; Lapierre et al, 2018 for meta-analytic evidence), organizational work–family support (i.e., behaviors of organizational members that are supportive of individual’s family roles; Hammer et al, 2009) has also been shown to positively affect the work domain by fostering the creativity of those employees receiving greater support (McKersie et al, 2019), and its reach even extends to improving the work-based relationships of employees’ partners (Booth-LeDoux et al, 2020). While this rich research stream has provided useful insights into the enriching effects of work–family support on dual-earner couples’ home and work lives, it is not matched by an equally rich understanding of (a) who is best suited to provide work–family support at work, (b) how work–family support affects both home and work domains, and (c) when work–family support is more likely to promote positive consequences for dual-earner couples.…”
mentioning
confidence: 99%